Methane production in the Yangtze River Estuary and East China Sea in 2019/2020 - Shi-Hai Mao; Hong-Hai Zhang; Guang-Chao Zhuang; Xiao-Jun Li; Qiao Liu; Zhen Zhou (PANGAEA, 2022)
We investigated the dynamic of methane concentration, saturation, and sea-to-air flux in the typical near-shore (Yangtze River Estuary) and outer shelf (East China Sea) areas. We further determined microbial methane production and the dynamic of aerobic methanotrophic activity employing in vitro radiotracer assay. The data presented here are beneficial to advancing our understanding for the methane cycle in the estuarine and shelf regions. This dataset includes the CH4 production during incubations with additions of methanogenic substrates in nearshore and offshore waters of the Yangtze River Estuary and East China Sea. Water samples of methane production experiments were collected from the Yangtze River Estuary and East China Sea aboard the R/V “Dongfang hong 3”and “Xiangyang hong 18” during two expeditions in December 2019 to January 2020 and May to June 2020. Seawater samples were collected directly using a 12 L Niskin bottle deployed on a Seabird 911 CTD rosette system, from which seawater temperature, salinity and depth were recorded. Methane production culture experiments were conducted in 125 mL acid-washed and sterilized serum vials filled with seawater and methane samples were measured using the headspace method. Each sample was shaken on a vortex mixer for 2 min to equilibrate the gas-liquid prior to gas extraction and 0.1-1 mL subsamples from the headspace were injected into GC-8890 using a gas-tight syringe.